Entangled Histories of the Balkans - Volume Two : Transfers of Political Ideologies and Institutions. - Daskalov, Rumen (Balkan studies library., 2013)
The authors in this volume seek to treat the modern history of the Balkans from a transnational and relational perspective in terms of shared and connected, as well as entangled, histories, transfers and crossings.